A intersubjetividade em sentenças judiciais - Frêitas, Ariádne Castilho de (2008)
This work is part of the research field Language and Work, and was based on six civil judicial sentences generated by first degree law judges in the state of São Paulo, between 2002 and 2006. This thesis intended to contribute as a way of enhancing the linguistics-enunciativediscursive knowledge of the judicial sentence, one of the tools of the magistrate. Moreover, it aimed to a) investigate the prescriptions for the sentence genre and whether or not the magistrate approaches or keeps away from them, resulting in stable or unstable structures; b) identify the linguistic-argumentative strategies used by the judge as a means of building his discourse; c) perceive how the judge inserts himself as a speaker and how the other is established, as well as it investigated who he(they) is(are); d) to analyze the voices/discourses in the sentences and how they can aid to build meaning. The hypothesis was that the sentences have coercions guaranteeing their stability. However, they presented non expected variations, for example, the outstanding presence of the other. In relation to the conflict between regularities and irregularities, it could be stated that the judge is the author of a discourse marked by intersubjectiveness, which contains different voices so as to convince the interlocutors that the decisions of the judge are valid. The methodology was based on the dialogic discourse analysis/theory, and some of its main concepts showed are the enunciation, dialogism, author-authorship, the discourse of the other, the language s plurality and the discourse genre from Bakhtin and his Circle. The works of Benveniste concerning enunciation and intersubjetiveness were relevant for this research. Some concepts about the Judiciary were researched in Law, and the conceptions of rhetoric and argumentation, based on Aristotle, Perelman and Ferraz Junior were searched in Philosophy. The results of the analysis demonstrated that the judicial sentence has coercions regulated by law. Nevertheless, it has some instabilities and revealed a lack of articulation between the prescribed and the accomplished work. It was identified that the judge adopts linguistic argumentative strategies, like verbs in the first person, as well as authority arguments to legitimate his magistrate position. In spite of the outstanding presence of the others and their voices in the magistrate sentences, it is considered that the judge is the author-creator of the sentence, because different social values could be appointed in such sentences. It is presented a discursive concept for the sentence: sentence is dialog, answer, and the legal doctrinaire judicial point of view is abandoned. This work contributes to the scientific sphere, as there are almost no works in this field concerning the judicial sentence in bakhtinian perspective